Virtual simulation with AneuShape™ software for microcatheter shaping in intracranial aneurysm coiling: a validation study - Wu, Zeng-Bao; Zeng, Ying; Zhang, Hua-Qiu; Shu, Kai; Li, Gao-Hui; Xiang, Jian-Ping; Lei, Ting; Zhu, Ming-Xin (Frontiers in Neurology, 2023)
Background The shaping of an accurate and stable microcatheter plays a vital role in the successful embolization of intracranial aneurysms. Our study aimed to investigate the application and the role of AneuShape™ software in microcatheter shaping for intracranial aneurysm embolization. Methods From January 2021 to June 2022, 105 patients with single unruptured intracranial aneurysms were retrospectively analyzed with or without AneuShape™ software to assist in microcatheter shaping. The rates of microcatheter accessibility, accurate positioning, and stability for shaping were analyzed. During the operation, fluoroscopy duration, radiation dose, immediate postoperative angiography, and procedure-related complications were evaluated. Results Compared to the manual group, aneurysm-coiling procedures involving the AneuShape™ software exhibited superior results. The use of the software resulted in a lower rate of reshaping microcatheters (21.82 vs. 44.00%, p = 0.015) and higher rates of accessibility (81.82 vs. 58.00%, p = 0.008), better positioning (85.45 vs. 64.00%, p = 0.011), and higher stability (83.64 vs. 62.00%, p = 0.012). The software group also required more coils for both small (<7 mm) and large (≥7 mm) aneurysms compared to the manual group (3.50 ± 0.19 vs. 2.78 ± 0.11, p = 0.008 and 8.22 ± 0.36 vs. 6.00 ± 1.00, p = 0.081, respectively). In addition, the software group achieved better complete or approximately complete aneurysm obliteration (87.27 vs. 66.00%, p = 0.010) and had a lower procedure-related complication rate (3.60 vs. 12.00%, p = 0.107). Without this software, the operation had a longer intervention duration (34.31 ± 6.51 vs. 23.87 ± 6.98 min, p < 0.001) and a higher radiation dose (750.50 ± 177.81 vs. 563.53 ± 195.46 mGy, p < 0.001). Conclusions Software-based microcatheter shaping techniques can assist in the precise shaping of microcatheters, reduce operating time and radiation dose, improve embolization density, and facilitate more stable and efficient intracranial aneurysm embolization.